The Analysis Of Children's Education Implementation That Involves Criminal At Child Development Institute - Chandra Sujana (JED (Jurnal Etika Demokrasi), 2020)
Abstract. Every Indonesian people is required to get basic education. Correctional students who in fact are criminals still get their rights to obtain an education, one of them by pursuing equality education from Package A, Package B, and Package C. Children that undergoing of punisment have rights to receive same education just like other normal childrens. . During this time the education of Childrens with Legal Issues (ABH) was ignored in terms of educators and facilities in LPKA. This research aims to determine the implementation of the Education package carried out in LPKA. The study and research used a qualitative approach by conducting direct observation as primary data. Secondary data in the form of literature studies sourced from verified official accounts and official government accounts. The results showed several factors that emerged in their education process, namely the lack of educators, lack of focus when learning and same and monotonous methods during the learning processKeywords: Children, Criminal Justice System for Children, EducationAbstrak.  Setiap warga negara Indonesia wajib mengikuti pendidikan dasar. Anak didik pemasyarakatan yang notabene adalah pelaku tindak kriminal tetap mendapatkan hak-haknya untuk memperoleh pendidikan yang layak, salah satunya dengan mengikuti pendidikan kesetaraan kejar Paket A, Paket B, dan Paket C. Anak yang sedang menjalani pidana berhak mendapatkan pendidikan yang sama dengan anak normal lainnya. Selama ini tingkat pendidikan Anak Bermasalah dengan Hukum (ABH)  kurang diperhatikan dari sisi tenaga pendidik maupun fasilitas yang ada di LPKA. Penelitian ini bertujuan untuk mengetahui pelaksanaan pendidikan kejar paket yang di laksanakan di LPKA. Penelitian menggunakan pendekatan kualitatif dengan melakukan observasi langsung sebagai data primer. Data sekunder berupa studi literatur yang bersumber dari akun resmi yang telah terverifikasi dan akun resmi pemerintah. Hasil penelitian menunjukan beberapa factor yang muncul pada proses pendidikan mereka yaitu kurangnya tenaga pendidik, kurangnya focus saat pembelajaran dan metode yang monoton saat proses pembelajaran.Kata Kunci: Anak, Pendidikan, Sistem Peradilan Pidana Anak